Let's name the first number x and the next number x + 1. So,
x^2 - (x + 1)^2
= x^2 - (x^2 + 2x + 1)
= x^2 - x^2 - 2x - 1
= - 2x - 1
= -(2x + 1)
Thus we can say that, the difference between the squares of two consecutive numbers is equal to the opposite of their sum (means it is their sum, but as a negative number).
Let's do some examples:
2, 3; 2 + 3 = 5
2^2 - 3^2 = 4 - 9 = -5 ( 5 and -5 are opposite numbers, and 5 is the sum of 2 and 3)
13, 14; 13 + 14 = 27
13^2 - 14^2 = 169 - 196 = -27 (27 and -27 are opposite numbers, and 27 is the sum of 13 and 14)
Chat with our AI personalities
Just check the squares of a few whole numbers. If 55 is between two of those squares, then its square root is also between the corresponding square roots.
The numbers are 13 and 14.
3 and 5
7 and 9 72+92 = 130
The numbers are 12 and 14.